Exploring the Medicinal flora of district Musakhel, Pakistan: A DNA Barcoding and Ethnobotanical Investigation - Kanwal, Razia; Irfan, Shanzia; Ahmed, Hina Ali; Ullah, Saad; Channa, Farah Naz; Ahmed, Nazeer (Ethnobotany Research and Applications, 2024)
Background: District Musakhel in Pakistan is known for its unique geographical and climatic conditions, fostering diverse flora and fauna, including unexplored medicinal plants. This study aims to systematically categorize these medicinal plant species using traditional taxonomic methods and advanced DNA barcoding techniques. Methods: The methodology included the ethnobotanical study and plant sampling, DNA extraction, PCR amplification of rbcL and ITS2 regions, sequencing, and subsequent taxonomic identification using BLAST and Phylogenetic analysis via the Neighbor-Joining method. Results: The rbcL barcode exhibited efficacy in discerning taxonomic relationships at the familial and generic levels, while the ITS2 barcode excelled in elucidating species-specific variations, albeit encountering challenges in clustering species within families. Nevertheless, the most precise taxonomic resolution was achieved by combining both barcodes. Furthermore, Phylogenetic tree analysis confirmed the effectiveness of the rbcL over ITS2 and the combined barcoding approach. The rbcL tree displayed robust performance, with 76.9% of nodes surpassing the 50 bootstrap value threshold and successfully resolving 85% of the studied species. The ITS2 tree, while weaker, still resolved 65% of the species. The combined analysis, integrating rbcL and ITS2 data, achieved a 58% success rate in species resolution. This research explored the ethnobotanical features, highlighting that Plantago major had the highest utilization among the species surveyed. Cirsium shansiense showed the greatest use value (0.37), while Ficus palmata and Solanum xanthocarpum had the highest Relative Frequency of Citation (RFC) values. Conclusions: In a nutshell, this study serves as a foundational contribution to thoroughly document, precisely identify, and conserve the priceless indigenous medicinal plant species in District Musakhel. Keywords: DNA Barcoding, Ethnobotany, ITS2, Phylogenetic, rbcL, Species Resolution.